2018
DOI: 10.1002/jcp.26624
|View full text |Cite
|
Sign up to set email alerts
|

LINC00968 functions as an oncogene in osteosarcoma by activating the PI3K/AKT/mTOR signaling

Abstract: Osteosarcoma is recognized as a malignant tumor in the skeletal system. Long non-coding RNAs (lncRNAs) have been exhibited to play crucial roles in osteosarcoma development. Our current study focused on the biological effects and mechanism of LINC00968 in osteosarcoma pathogenesis. We observed that LINC00968 was dramatically elevated in osteosarcoma cells including U2OS, MG63, Saos-2, SW1353, and 143-B cells compared to human osteoblast cell line hFOB. Silence of LINC00968 inhibited osteosarcoma cell growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Previous studied showed that LINC00968 acted crucial roles in the development of nonsmall cell lung cancer and osteosarcoma . For example, Wang et al identified that LINC00968 expression level was upregulated in nonsmall cell lung cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studied showed that LINC00968 acted crucial roles in the development of nonsmall cell lung cancer and osteosarcoma . For example, Wang et al identified that LINC00968 expression level was upregulated in nonsmall cell lung cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is frequently hyperactivated in osteosarcoma, and contributes to disease initiation and development (37). Moreover, inhibition of this pathway via small compounds is a potential therapeutic approach for osteosarcoma (38). Previous studies have shown that Wilms' tumor 1 knockdown in MG-63 cells results in deregulation of cell cycle proteins and downregulation of the PI3K/AKT pathway (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00968 was rst identi ed by Hui et al in 2015, and the following researches demonstrated its diverse role in different human cancers. LINC00968 inhibited the progression of breast cancer yet acted as an oncogene in epithelial ovarian cancer and osteosarcoma [8][9][10]12]. Here in our study, we investigated the exact role of LINC00968 in the progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing evidences revealed that lncRNAs are involved in numerous human diseases, cancer included, full understanding of their exact molecular mechanisms is still far beyond completion [7]. Long intergenic non-protein coding RNA 968 (LINC00968) is reported to be dysregulated in several human cancers including breast cancer, osteosarcoma, and epithelial ovarian cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%